Environmental profile of sweet sorghum bioethanol in the province of Tucumán (Argentina) - Garolera De Nucci, Lorena Patricia (2023)
Objectives: The objective of this study is to evaluate the environmental profile of bioethanol production from sweet sorghum (Sorghum bicolor (L.) Moench) in the province of Tucumán (Argentina). Methods: The study is carried out using the life cycle assessment (LCA) methodology. The evaluated system includes the cultivation of sorghum, its transportation to the sugar mill, and the production of anhydrous ethanol. For the inventory, data recorded in field/industry activities is preferably used, supplemented by specialized publications and the Ecoinvent v3 database. The ReCiPe 2016 impact evaluation model is used to obtain the environmental profile. Results and discussion: The results show that the environmental contribution of the sorghum agricultural phase dominates all impact categories, mainly due to the use of some agrochemicals and fossil fuels. The normalization of these results highlights freshwater ecotoxicity as the most relevant category. The sensitivity analysis reveals that this category depends almost linearly on the leaching-runoff factors of the pesticides, among which chlorpyrifos prevails. Conclusions: This study unveils the hotspots in sorghum bioethanol production, which will be used to improve the agronomic management of the crop and processing. The incorporation of sorghum as a feedstock in the existing cane-based sugar-alcohol industry allows for a significant reduction of the global warming potential, opening opportunities for future research on the subject. Therefore, the cultivation/processing of sweet sorghum is a promising alternative to reduce the environmental impact of ethanol from other sugarcane-producing regions.